Analisa Waktu Pelaksanaan Pekerjaan Menurut Analisa (AHSP) 2016 Bidang Bina Marga - Ardhana, Angga Tresna; Syahruddin, - (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
This research is motivated to can know the definite schedule of work that has been set in the auction process, in which the determination was based solely on the experience of the tender committee of the work previous work, without any calculation basis is clear, and aims to make an analysis of scheduling by using analysis AHSP 2016 of Bina Marga, and make a comparison of the results of calculations using 2016 AHSP method of Bina Marga with the usual standard calculation is made .This type of research is the Employment Unit Price Analysis (AHSP) 2016 Field Development Bina Marga, where On regulation of Minister (PERMENPU) NO: 11/2013on November 4, 2013 article 1 mentioned that, this Code establishes the steps calculate the price of the basic unit (HSD), wages, labor, tools, and materials which then calculate the unit price (HSP) ,.from this studyThe normal time schedule planner find aan longer that 87 days, this time more than 12 days of work in the contract planing time of only 75 days, and the cost of the normal work has 9.990.726.446, because the normal time counter exceeds the time on the job then the work done or the program crashes additional work time.Application Both calculations should be calculated simultaneously, which is useful as a comparison in the calculation to obtain the closest value estimate in the bid owner.Â Keywords : 2016 AHSP of Bina Marga, Unit Price Analysis